PERAN PEREMPUAN DALAM PENGEMBANGAN EKONOMI DAERAH PADA UMKM: Studi Kasus Pada Pemilik UMKM Di Wilayah Solo Raya - Sumarmawati, Eka Dewi; Rachman, Arif Nugroho (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
The purpose of this research is to test the influence gender differences, level of education and business age to income of Small Medium Enterprises (SMEs) in Solo Raya. This researcher will analyze the influence gender differences, the level of education and business age towards the income of SMEs in Solo Raya. There are more than 960 SMEs managed by government of Solo Raya. In order to analyze the data, the collection of data is done through survey and interview to the owners of SMEs in Solo Raya. The researcher utilizes ordinary linier regression analysis SPSS program while the sample size is 150 owners of SMEs. Results show that gender, level of education and business age differences significantly influences the income of the SMEs.